ANALISIS KEBIJAKAN DIGITALISASI PENDIDIKAN DASAR: RELASI TEKNOLOGI PENDIDIKAN, PEMERINTAHAN, DAN DINAMIKA SOSIAL GLOBAL - Defi Defi (Pelantar Press, 2026)
This study aims to analyze the policy of digitalization in primary education by examining the relationship between educational technology, governance, and global social dynamics. Educational digitalization is understood not merely as the utilization of technological devices, but as a comprehensive transformation of learning systems and educational governance. This research employs a qualitative approach with a public policy analysis design, utilizing document analysis and in-depth interviews with key stakeholders in primary education. The findings indicate that the digitalization policy developed by Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi represents a strategic response to rapid global digital transformation and the demand for 21st-century competencies. However, policy implementation continues to face significant challenges, including infrastructural disparities, unequal digital literacy among teachers, and regional social inequalities. Furthermore, global dynamics and recommendations from international organizations such as UNESCO have influenced the direction of national education policy. The study concludes that the success of primary education digitalization depends on equitable access to technology, strengthened human resource capacity, and inclusive and socially just governance frameworks.